Gastrointestinal system involvement characteristics in Covid -19 patients - Atasoy, Halil; Urcar, Vehbi (Journal of the Pakistan Medical Association, 2025)
Objective: To evaluate the involvement of gastrointestinal tract features in patients of coronavirus disease-2019, and to analyse the effects of these features on the development of critical illness, macrophage activation syndrome and mortalit Method: The retrospective, cross-sectional study was conducted from January 2021 to December 2022 at a tertiary care facility after approval from the ethics review committee of Recep Tayyip Erdogan University, Turkiye, and comprised data from March 30, 2020, to March 31, 2022, related to coronavirus disease-2019 inpatients. Gastrointestinal features, including nausea, vomiting, abdominal pain, diarrhoea, gastrointestinal bleeding, weight-loss and anorexia, and laboratory findings related to aspartate transaminase, alanine transaminase, total bilirubin, direct bilirubin, indirect bilirubin, alkaline phosphatase, gamma glutamyl transferase, amylase, C-reactive protein and ferritin levels were evaluated. The effects of biomarkers, clinical symptoms and findings on the development of macrophage activation syndrome, as well as the relationship with the development of critical illness and the effects on mortality were evaluated. Data was analysed using SPSS 22.0 statistical package program. Results: Of the 2,154 patients, 1,150(53.4%) were males and 1,004(46.6%) were females. The overall mean age was 61(61±16.8) years (range: 18-90 years). A total of 109(5.1%) patients died, 195(9.1%) developed critical illness and 158(7.3%) developed macrophage activation syndrome. Gastrointestinal symptom anorexia had significant association with the development of macrophage activation syndrome and mortality (p<0.05). There was a statistically significant relationship between nausea a and development of critical illness (p <0.012). Macrophage activation syndrome, critical illness and mortality were significant in patients with high ferritin levels (p<0.05). There was a significant relationship of high alanine transaminase levels with macrophage activation syndrome and critical illness (p<0.05). High aspartate transaminase levels were significantly associated with macrophage activation syndrome, critical illness and mortality (p<0.05). There was a significant association of elevated amylase levels with macrophage activation syndrome and mortality (p<0.05). High gamma glutamyl transferase levels were significantly associated with macrophage activation syndrome, critical illness and mortality (p<0.05). Conclusion: Gastrointestinal feature anorexia and elevated levels of aspartate transaminase, alanine transaminase, gamma glutamyl transferase and amylase were found to be associated with poor prognosis in coronavirus disease-2019 patients. Key Words: COVID-19, GI uptake characteristics, C-reactive protein, Ferritin, Macrophage activation syndrome, Liver function tests.